Determinants of banking health in ASEAN on dividend policy - M. Arief Nur Wibowo Hartas; Isni Andriana; Shelfi Malinda; Marlina Widiyanti (Interdisciplinary Social Studies, 2025)
This study was conducted to determine the effect of capital adequacy ratio (CAR), product asset quality (KAP), return on assets (ROA), net profit margin (NPM), financing to deposit ratio (FDR), and their impact on dividend payout ratio (DPR). This study contributes to the understanding of financial performance and dividend policies in the banking sector by examining the relationships between key financial metrics. The results show that the CAR has a positive and significant effect on dividend policies for banking companies in ASEAN. The quality of product assets has an important effect on the dividend policy of property, real estate, and building construction companies listed on the Indonesia Stock Exchange. The FDR is a negative and insignificant factor that affects dividend policies. The findings can inform banking institutions in formulating strategies to optimize their financial performance while maintaining an attractive dividend policy. This study provides valuable insights for stakeholders, including investors, management, and policymakers, on how financial health and operational efficiency can affect shareholder returns.